2022
DOI: 10.1161/strokeaha.121.038216
|View full text |Cite
|
Sign up to set email alerts
|

Intraarterial Nimodipine Versus Induced Hypertension for Delayed Cerebral Ischemia: A Modified Treatment Protocol

Abstract: Background: Rescue treatment for delayed cerebral ischemia (DCI) after subarachnoid hemorrhage can include induced hypertension (iHTN) and, in refractory cases, endovascular approaches, of which selective, continuous intraarterial nimodipine (IAN) is one variant. The combination of iHTN and IAN can dramatically increase vasopressor demand. In case of unsustainable doses, iHTN is often prioritized over IAN. However, evidence in this regard is largely lacking. We investigated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…30,31 In contrast, in a setting with induced hypertension and vasodilation together, we found that a higher pressure target (>180 mmHg systolic) corresponded to even lower PbtO 2 values than a lower pressure target (>120 mmHg systolic). 32 As a future prospect, analyzing the relationship of deltaCPP and PbtO 2 during phases with induced hypertension may delineate an upper limit of autoregulation, and give insight into the oxygen-plus that can or cannot be expected by hypertensive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 In contrast, in a setting with induced hypertension and vasodilation together, we found that a higher pressure target (>180 mmHg systolic) corresponded to even lower PbtO 2 values than a lower pressure target (>120 mmHg systolic). 32 As a future prospect, analyzing the relationship of deltaCPP and PbtO 2 during phases with induced hypertension may delineate an upper limit of autoregulation, and give insight into the oxygen-plus that can or cannot be expected by hypertensive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary systemic distribution of the vasodilator often increases the vasopressor demand to counteract this effect peripherally ( 16 ). Weiss et al ( 17 ) investigated the potential of induced hypertension vs. continuous intra-arterial nimodipine infusion as a rescue treatment for DCI. In the latest guidelines, induced hypertension is the recommended primary rescue therapy and intra-arterial spasmolysis is an adjunct with the weaker recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…Weiss et al, 18 describe that although IAN was locally administered, it often resulted in hypotension, relative to the standard of care goal of systolic blood pressure >180 mm Hg, or absolute hypotension, related to the systemic vasodilatory effects of nimodipine. The reduced blood pressure, compared with the threshold set, required a high dose of vasoactive drips (mainly norepinephrine).…”
mentioning
confidence: 99%
“…In the current issue of Stroke , Weiss et al 18 published a retrospective analysis of a pre/post change in their usual care protocol. In the original clinical protocol, all patients with clinical DCI or high-risk patients (for examples those with perfusion deficit on CT-perfusion, or a significant reduction in partial pressure of brain tissue oxygen—P ti O 2 ) were treated with induced hypertension.…”
mentioning
confidence: 99%
See 1 more Smart Citation